DESKRIPSI KINERJA PRODUK WIRAUSAHA WANITA DALAM MENDUKUNG SDGS & ASTA CITA - Sulung Rahmawan Wira Ghani; Syai'in; Agus Sulthon; Kusnul Ciptanila Yuni K (Smart Education, 2026)
The role of female entrepreneurs in the business world is increasingly growing, no longer dominated by men, but also by women who are now actively participating as business owners. The main characteristic of female entrepreneurs is their ability to manage time flexibly, especially for those who are married, allowing them to run a business while taking care of their families. Factors that encourage women to become entrepreneurs include emancipation, higher education, the desire to support family economics, and opportunities for personal development. The presence of female entrepreneurs also contributes to the achievement of the Sustainable Development Goals (SDGs), such as poverty eradication (Goal 1), gender equality (Goal 5), decent work and economic growth (Goal 8), and reduced inequalities (Goal 10). Furthermore, with the growing interest in religious tourism, female entrepreneurs play a crucial role in supporting the economic movement in this sector while also contributing to the realization of Asta Cita, the noble ideals of creating shared prosperity. This study aims to explore the role of female entrepreneurs in the religious tourism industry area of Tebuireng, particularly in relation to the SDGs and Asta Cita, and their contribution to more inclusive and sustainable economic and social development. The results of this study show that the contribution of products offered by women entrepreneurs in the religious tourism area is as follows: Cluster 1 contains the same products, accounting for 48% (48 sample data), Cluster 2 contains the same products, accounting for 11% (6 sample data), Cluster 3 contains the same products, accounting for 35% (19 sample data), and Cluster 4 contains the same products, accounting for 6%.